WANITA MALAM DALAM HEGEMONI SUPERSTRUKTURAL: PERSPEKTIF TEORI KRITIS (PENELITIAN TERHADAP GADIS MALAM MOTOR MATIK DI KOTA CIREBON) - Abdul Karim (Universitas Islam Negeri Fatmawati Sukarno, 2015)
: Cirebon is the “heart” of the city for several districts of Indramayu, Majalengka and Kuningan. It got the nickname as a city guardian, with the mandate of Sunan Gunung Jati, “Ingsun titip tajug lan fakir Miskin”. But when night falls, the identity of religious life of the town mayor as if suddenly changed, especially on Friday night. At one particular congregation, pilgrims flock to the Tomb guardian, but the other party actually visited the place dimly lit stalls (night cafe) inhabited by girls night. This study will answer questions about how the hegemony of the superstructure of the girl automatic motor night in the city of Cirebon? What public opinion against the social status of girls night? What reasons are causing the girls night hung in night cafe? By doing so, is there any indication of gender equality that they want? What is done by allowing the establishment apparatus dimly lit stalls and jasmine is a form of superstructural hegemony. This is an indication that they are officials with direct and intentional nurture girls selling themselves for a night at the venue. Thus, the authorities will benefit from what they do.